Testing Method for Non-Isothermal Radial Wall Jets from Ceiling Diffusers Used in Building Ventilation - Maria Hurnik (Energies)
Diffusers producing radial jets attached to the ceiling are most often used in ventilation and air conditioning systems. In building ventilation, the temperature of the jet supplying the air into the rooms is usually different to the surrounding air temperature. To save energy for air transportation during periods of low heat gains, the air flow should be reduced as low as possible, to about 20% of its nominal value. A significant decrease in the air flow supply in cooling mode may cause cold air dumping and, consequently, increase the risk of local discomfort due to drafts in the occupied zone. In this study, a method for assessing the effect of non-isothermality on the speed distribution of radial wall jets has been developed. The measured terminal speed isolines, W = 0.2 m/s, were compared with the isolines determined for isothermal jets. The test results have shown that, for radial wall jets supplying air at an Archimedes number higher than approximately 50 × 10−4, the risk of jet dumping is significant.